Ingestion of Porphyromonas gingivalis exacerbates colitis via intestinal epithelial barrier disruption in mice - Tsuzuno, Takahiro; Takahashi, Naoki; Yamada‐Hara, Miki; Yokoji‐Takeuchi, Mai; Sulijaya, Benso; Aoki‐Nonaka, Yukari; Matsugishi, Aoi; Katakura, Kyoko; Tabeta, Koichi; Yamazaki, Kazuhisa (Journal of periodontal research, 2021)
Objective This study aimed to evaluate the effects of ingested periodontal pathogens on experimental colitis in mice and to elucidate its underlying mechanisms. Background Inflammatory bowel disease (IBD) is defined as a chronic intestinal inflammation that results in damage to the gastrointestinal tract. Epidemiological studies have shown an association between IBD and periodontitis. Although a large number of ingested oral bacteria reach gastrointestinal tract constantly, the effect of ingested periodontal pathogens on intestinal inflammation is still unknown. Methods Experimental colitis was induced by inclusion of dextran sodium sulfate solution in drinking water of the mice. Major periodontal pathogens (Porphyromonas gingivalis, Prevotella intermedia, and Fusobacterium nucleatum) were administered orally every day during the experiment. The severity of colitis between the groups was compared. In vitro studies of the intestinal epithelial cell line were conducted to explore the molecular mechanisms by which periodontal pathogens affect the development of colitis. Results The oral administration of P. gingivalis significantly increased the severity of colitis when compared to other pathogens in the DSS‐induced colitis model. The ingested P. gingivalis disrupted the colonic epithelial barrier by decreasing the expression of tight junction proteins in vivo. In vitro permeability assays using the intestinal epithelial cell line suggested the P. gingivalis‐specific epithelial barrier disruption. The possible involvement of gingipains in the exacerbation of colitis was implied by using P. gingivalis lacking gingipains. Conclusion Porphyromonas gingivalis exacerbates gastrointestinal inflammation by directly interacting with the intestinal epithelial barrier in a susceptible host.